Developing sustainable development competencies in university students: academic expectations and labor market requirements - Bespalyy, Sergey; Bespalaya, Yelena (Frontiers in Education, 2026)
In the context of the global labor market transformation caused by technological change and the need to achieve the Sustainable Development Goals (SDGs), developing sustainable development (SD) competencies in university graduates is becoming a key factor in their competitiveness. The aim of the study was to identify and analyze the needs of Kazakhstani employers for SD competencies in graduates of technical and humanities specialties, as well as to assess the level of awareness among the academic and business communities. The empirical base consisted of a questionnaire and interviews with respondents from five cities of Kazakhstan. The results revealed a significant gap between the declarative importance of SD and its operational understanding. Sectoral differences were identified: in the technical sector, systems thinking and strategic foresight are most in demand, while in the humanities, normative and interpersonal competence are in high demand. A deficit in these competencies among graduates was identified. The results underscore the need for targeted integration of SD competencies into educational programs through curriculum updates, the development of project-based learning, and stronger ties with industry.